Establecimiento del proceso de disposición de residuos sólidos y peligrosos en una empresa que presta servicios para el tratamiento químico en el sector petrolero (2020)
This study is based on the hazardous waste management produced by small and medium-sized enterprises (SMEs) that provides the chemical treatment service in the oil fields. The hazardous waste comes mainly from the containers impregnated with liquid chemicals used in the oil field. This study was completed in three stages: 1) Description of the activities that the SMEs do in the fieldwork and the warehouse in order to identify which are the ones that generate more hazardous waste; 2) Standardization of the hazardous waste management process based on the previous description to provide an adequate final disposition, and 3) Elaboration of an assessment for the hazardous waste management process, identifying successes and failures of the disposal process carried out in the SME.